Changes in the intensive english program at the Lebanese American University in Beirut, Lebanon - Bahous, Rima (2001)
The Curriculum of the Intensive English Program (IEP) established in the mid- twentieth century at the Lebanese American University (LAU) has been reviewed several times. However, since the 1970s, the minor changes that have been implemented to the program structure and content needed to be reviewed in relation to students' changing needs in post-war Lebanon. The present study through action research is an attempt to identify relevant program weaknesses and propose solutions. This study overviews what the program used to be and focuses on the changes that occurred and were implemented in the past years and up to Summer 1999. The basis of the research undertaken at the university is the data collected through questionnaires, interviews, observation, document analysis, and discussion with staff and students. Thus, through triangulation, a multi-method approach, was achieved. The findings show that throughout the various cycles of the action research (participatory and emancipatory), the program was slowly but surely modified. Innovations were implemented, evaluated, and changed; thus, from a skill-oriented syllabus to a task-based language approach with an emphasis on academic writing skills, a huge step far from the traditional approach in teaching has been reached. Learners' needs are prioritized, and integration of all language skills is adopted in the program. Collaboration among the students, IEP faculty, and the researcher has strengthened the team spirit established because of the action research. Not only did the changes trigger the motivation of the learners but it also allowed the IEP staff to become more innovative in their approach to language teaching. However, and action research is a never-ending cycle; this research is far from being completed. The years to come should see new changes in order to continue what has already been achieved.